The Role of Academies in the 21st Century: Knowledge in the Age of Relativism - von Feigenblatt, Otto F. (Caminos educativos, 2022)
The present paper presents a brief overview of the development of academies and how their role has evolved during the centuries. At the core of the mission of academies one can find the concept of “knowledge” and its “diffusion”. A brief discussion about the importance of knowledge in the age of data and information is provided so as to explain the pivotal function of Academies vis a vis universities, the media, and governments. A final section discusses the challenges and opportunities faced by academies in an age characterized by extreme relativism and virulent populism.